Membangun Lingkungan Anti Bullying di Panti Asuhan Ar-Rahman - Suafisa, Haydi; Ritonga, Fajar Utama; B, Bengkel (Yayasan Daarul Huda Kruengmane, 2025)
The author conducted a practicum at the Ar-Rahman Orphanage on Jl. Arifin No.1a, Sitirejo II, Kec. Medan Amplas, Medan City, North Sumatra 20217. The practicum conducted by the author was to research the problems experienced by the orphanage children. The problems experienced by the orphanage children were being victims of bullying. From this problem, the author was interested and had the goal of helping the problems of the children in the orphanage by saying that when we are experiencing bullying, we must do it by facing bullying, such as daring to speak up, seeking support from adults, and avoiding dangerous confrontations. The author has clients (individuals) who experience these problems. The clients consist of children who are still in elementary school (SD) grade 2. The author uses the Casework stage in his research from the preparation stage to the termination stage. After carrying out all the casework stages, the results expected by the author are that the orphanage children (clients) can show positive development and be able to face social situations better.